2011
DOI: 10.1186/1478-4505-9-3
|View full text |Cite
|
Sign up to set email alerts
|

Does mass drug administration for the integrated treatment of neglected tropical diseases really work? Assessing evidence for the control of schistosomiasis and soil-transmitted helminths in Uganda

Abstract: BackgroundLess is known about mass drug administration [MDA] for neglected tropical diseases [NTDs] than is suggested by those so vigorously promoting expansion of the approach. This paper fills an important gap: it draws upon local level research to examine the roll out of treatment for two NTDs, schistosomiasis and soil-transmitted helminths, in Uganda.MethodsEthnographic research was undertaken over a period of four years between 2005-2009 in north-west and south-east Uganda. In addition to participant obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
207
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 169 publications
(214 citation statements)
references
References 35 publications
5
207
1
1
Order By: Relevance
“…In other words, deworming alone was largely ineffective. Since 2005, research undertaken by the authors and their students has found comparable problems in other parts of East Africa (Aldis, 2008;Wingate-Saul & Shira, 2008;Parker et al, 2008Parker et al, , 2012Parker & Allen, 2011, 2013aOzunga, 2014;Pearson, 2016;Hastings, 2016). Field sites were located in north-western Uganda (Nebbi, Buliisa, Adjumani and Moyo Districts), south-eastern Uganda (Busia District -just across the border from where Miguel and Kremer studied deworming in Kenya), Tanzania's Ukerewe Island in Lake Victoria, Tanga Region in northern coastal Tanzania, and Morogoro Region, which lies to the west of Dar es Salaam (see Fig.…”
Section: Doing Deworming In East Africamentioning
confidence: 90%
See 4 more Smart Citations
“…In other words, deworming alone was largely ineffective. Since 2005, research undertaken by the authors and their students has found comparable problems in other parts of East Africa (Aldis, 2008;Wingate-Saul & Shira, 2008;Parker et al, 2008Parker et al, , 2012Parker & Allen, 2011, 2013aOzunga, 2014;Pearson, 2016;Hastings, 2016). Field sites were located in north-western Uganda (Nebbi, Buliisa, Adjumani and Moyo Districts), south-eastern Uganda (Busia District -just across the border from where Miguel and Kremer studied deworming in Kenya), Tanzania's Ukerewe Island in Lake Victoria, Tanga Region in northern coastal Tanzania, and Morogoro Region, which lies to the west of Dar es Salaam (see Fig.…”
Section: Doing Deworming In East Africamentioning
confidence: 90%
“…With large numbers of children in under-resourced and rural parts of Uganda failing to complete their primary education, it proved problematic to extrapolate the findings to the wider school-aged population. Indeed, the study had to be stopped after 3 years, because so many children had dropped out of school (Parker & Allen, 2011). This last point would seem to counter Miguel and Kremer's finding in Kenya that deworming was linked to improved school attendance, but it may be largely explained by another factor.…”
Section: Evidence From Deworming Trialsmentioning
confidence: 97%
See 3 more Smart Citations